PERILAKU PENGGUNAAN DAN PERAWATAN KELAMBU LLINs PADA MASYARAKAT DAERAH ENDEMIS MALARIA KABUPATEN LEBAK PROVINSI BANTEN - Diana Andriyani Pratamawati; Siti Alfiah; Widiarti Widiarti (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2018)
The effectiveness of insecticide-treated nets are believed to reduce the prevalence of malaria is influenced by the behavior of people in their use , such as how to install and wash , in addition to duration of use . People's behavior can be different in each region with respect to culture , culture and ethnicity / ethnicity as a predisposing factor . The purpose of this study is to describe the behavior of people in the use of insecticide-treated nets ( LLINs ), such as the acceptance, use, washing and participation in the care of LLINs (program preservation).The study design was observational cross-sectional design. The instrument of this research is questionnaire and observation guidance of mosquito net. Samples are people with insecticide-treated nets in Lebak regency (Banten) were 81 respondents . Data were analyzed by descriptive. The results showed the level of knowledge about the use of mosquito nets in the category of " enough " (70,4 %) , with the majority being " support " the use of mosquito nets (65,4 %), and the practise of the use of mosquito nets were classified as " good " (58 %). The results also show the observation nets most respondents installing netting around the bed either owned or partially owned the bed.nowledge of the use of mosquito nets is not maximal and in the use of insecticide treated nets LLINs in a small number of respondents complained of heat and stifling, so it is necessary to evaluate the benefits of socialization activities and how to install and care of insecticide treated nets LLINs that have been done.